A novel orange-emitting LaBMoO6:Sm3+ phosphor. Issue 2 (15th January 2022) - Hu, Shanshan; Lu, Shuang; Hong, Ying; Yao, Aihua; Wang, Baolong; Li, Wei; Chu, Benli; He, Qinyu; Cheng, Jun; Wang, Yinzhen
Abstract: Sm 3+ doped LaBMoO6 phosphors were prepared by using the solid-state reaction method. The microstructure, morphology, chemical element composition, absorption, luminescent performance, decay life and thermal stability of Sm 3+ doped LaBMoO6 samples were studied. Sm 3+ doped LaBMoO6 phosphors mainly emit orange light at 596 nm with a decay lifetime of milliseconds under the excitation of 405 nm. The chromaticity coordinates of Sm 3+ doped LaBMoO6 samples are located in the orange region, which also have great thermal stability. The Sm 3+ doped LaBMoO6 phosphors can be used as orange-emitting materials in W-LED devices.